2012
DOI: 10.1371/journal.pone.0039856
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Profile of the Response of Two Soybean Genotypes to Potassium Deficiency

Abstract: The macronutrient potassium (K) is essential to plant growth and development. Crop yield potential is often affected by lack of soluble K. The molecular regulation mechanism of physiological and biochemical responses to K starvation in soybean roots and shoots is not fully understood. In the present study, two soybean varieties were subjected to low-K stress conditions: a low-K-tolerant variety (You06-71) and a low-K-sensitive variety (HengChun04-11). Eight libraries were generated for analysis: 2 genotypes ×2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 88 publications
(84 reference statements)
2
28
1
Order By: Relevance
“…The expression level of many genes related to ROS production and detoxification changed in this study, and this result is consistent with previous reports (Wang et al, 2012;Shankar et al, 2013). Among the genes, 3 cytochrome P450s were up-regulated, and P450 can regulate auxin synthesis in Arabidopsis (Bak et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…The expression level of many genes related to ROS production and detoxification changed in this study, and this result is consistent with previous reports (Wang et al, 2012;Shankar et al, 2013). Among the genes, 3 cytochrome P450s were up-regulated, and P450 can regulate auxin synthesis in Arabidopsis (Bak et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…In K ? -deficient cotton, Wang et al (2012a) and Bednarz et al (1999) observed a reduction in nitrate reductase activity and protein content, whereas the content of amino acids increased. Zhao et al (2001) reported the amount of increased sucrose in K-deficient cotton leaves was much higher than the amount of increased hexose.…”
Section: Introductionmentioning
confidence: 93%
“…Isobaric mass tagging (e.g., TMT and iTRAQ) is a precise and sensitive multiplexed peptide/protein quantification technique in mass spectrometry [22], which has been intensively used for revealing the proteins being differentially expressed under any given conditions, including biotic and abiotic stresses, such as heat stress [23] and Al stress [24]. Recently, some omics methods have been performed on some plants, for instance, rice [25], soybean [26] and watermelon [27], to investigate the underlying tolerance mechanism of plants to K deficiency, mostly at the transcriptional level. The barley proteomics can be mainly summarized as (a) industry driven biotechnology, including seed germination, beer proteomes, and malting proteomes and (b) biology driven proteomics, including abiotic stress tolerance and nitrogen use efficiency [28].…”
Section: Introductionmentioning
confidence: 99%